Computational fluid dynamics (CFD) simulation of liquid aerosol coalescing filters - Mead-Hunter, R.; King, Andrew; Kasper, G.; Mullins, Ben (Pergamon, 2013)
This work presents a new computational fluid dynamics model, developed to simulate the behaviour of fibrous filters used to treat liquid aerosols. We demonstrate that the solver can resolve the fundamental processes that occur in coalescing filters, such as aerosol droplet capture, coalescence, film break-up, and the motion of coalesced liquid droplets. Initial simulations were conducted on idealised geometries to ensure agreement between the simulations and existing theory, before simulations on more complex geometries were carried out, and finally simulations on realistic filter geometries. It is demonstrated that CFD can provide a viable alternative to whole-scale mist filter testing, particularly if high performance computational resources are available. Additionally, the paper includes a comprehensive treatment of the issues to be overcome when using Lagrangian methods to simulate nano-sized aerosols.